Integrated Care in the Era of COVID-19: Turning Vision Into Reality With Digital Health - Kouroubali, Angelina; Kondylakis, Haridimos; Katehakis, Dimitrios G. (Frontiers in Digital Health, 2021)
The lives of millions of people have been affected during the coronavirus pandemic that spread throughout the world in 2020. Society is changing establishing new norms for healthcare education, social life, and business. Digital health has seen an accelerated implementation throughout the world in response to the pandemic challenges. In this perspective paper, the authors highlight the features that digital platforms are important to have in order to support integrated care during a pandemic. The features of the digital platform Safe in COVID-19 are used as an example. Integrated care can only be supported when healthcare data is available and can be sharable and reusable. Healthcare data is essential to support effective prevention, prediction, and disease management. Data available in personal health apps can be sharable and reusable when apps follow interoperability guidelines for semantics and data management. The authors also highlight that not only technical but also political and social barriers need to be addressed in order to achieve integrated care in practice.